Peran Dukun Manten Dalam Prosesi Pernikahan Adat Jawa Di Kecamatan Rimbo Ulu Kabupaten Tebo Provinsi Jambi - Widyani, Ani Nur; Akbar, Waza Karia; Wijaya, Wibi (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research was dilatory by the role of Dukun Manten who still plays an active role in the implementation of Javanese traditional marriages in Suka Damai Village, Rimbo Ulu Dis- trict, Tebo Regency, Jamb Province. The role of the dukun manten is very important in the procession of the Javanese traditional wedding ceremony. The dukun manten must also be able to provide views on the planned event based on the experiences that have been carried out so that it is in accordance with what is expected by those who have the intention. As a result, the authors found that the role of the dukun manten in Suka Damai Village, Rimbo Ulu District, Tebo Regency, Jambi Province, which includes: 1. The role of the man- ten shaman in Suka Damai Village 2. Performing Siraman, 3. Installing paes, 4. Performing the Sembaga tradition, 5. Carrying out initi from the Javanese traditional ceremony, namely Temon btide.